Control of a Novel Spermatocyte-Promoting Factor by the Male Germline Sex Determination Factor PHF7 of Drosophila melanogaster. Issue 4 (1st August 2017) - Yang, Shu Yuan; Chang, Yi-Chieh; Wan, Yu Hsin; Whitworth, Cale; Baxter, Ellen M; Primus, Shekerah; Pi, Haiwei; Van Doren, Mark
Abstract: A key aspect of germ cell development is to establish germline sexual identity and initiate a sex-specific developmental program to promote spermatogenesis or oogenesis. Previously, we have identified the histone reader Plant Homeodomain Finger 7 (PHF7) as an important regulator of male germline identity. To understand how PHF7 directs sexual differentiation of the male germline, we investigated the downstream targets of PHF7 by combining transcriptome analyses, which reveal genes regulated by Phf7, with genomic profiling of histone H3K4me2, the chromatin mark that is bound by PHF7. Through these genomic experiments, we identify a novel spermatocyte factor Receptor Accessory Protein Like 1 (REEPL1) that can promote spermatogenesis and whose expression is kept off by PHF7 in the spermatogonial stage. Loss of Reepl1 significantly rescues the spermatogenesis defects in Phf7 mutants, indicating that regulation of Reepl1 is an essential aspect of PHF7 function. Further, increasing REEPL1 expression facilitates spermatogenic differentiation. These results indicate that PHF7 controls spermatogenesis by regulating the expression patterns of important male germline genes.